Kebebasan Yang Dikurasi: Peran Platform Digital Dalam Membatasi Ekspresi Publik - Muhammad Nadhif Judhananto; Fero Natanael; Thomas Tokan Pureklolon (Professional: Jurnal Komunikasi dan Administrasi Publik, 2026)
This study analyzes the paradox of freedom of expression in digital public spaces, particularly on social media platforms such as X, Instagram, YouTube, and TikTok. Social media is often perceived as a democratic space that enables individuals to voice opinions, share information, and participate in public discourse. However, this form of freedom is not entirely open; instead, it is constructed through algorithms, content moderation policies, and the economic-political logic of digital capitalism. The purpose of this research is to reveal how technological and institutional mechanisms within social media shape the boundaries of freedom of expression and their implications for the formation of public discourse. This research employs a qualitative approach using library study and conceptual analysis methods. The theoretical framework is based on Habermas’ concept of the public sphere, Foucault’s notion of power relations, and the theories of algorithmic governance and platform society. Data were analyzed descriptively and critically to examine the relationship between digital structures, power, and knowledge production. The findings indicate that algorithms and platform policies function as instruments of curation and control that determine content visibility, distribution, and legitimacy. Consequently, the digital public sphere is not entirely free but becomes an engineered arena shaped by economic interests and platform power. This condition also generates self-censorship practices among users and limits the diversity of discourses that emerge in digital public spaces. The study concludes that freedom of expression in the digital era is essentially “curated,” requiring critical awareness of the mechanisms that regulate the production and consumption of information.